PENGEMBANGAN MOBILE LEARNING MILEA D3 BERBASIS RME PADA MATERI DIMENSI TIGA - Erlyanna Nur Risqi; Wahyu Setyaningrum; Ratri Murdy Andari; Dyah Ayu Puspita Ardani (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Geometri merupakan cabang matematika yang wajib dipelajari. Salah satu materi geometri yang paling sulit untuk dipelajari adalah dimensi tiga, yang membutuhkan keterampilan visual dan spasial yang sangat tinggi. RME yaitu pendekatan pembelajaran yang mudah dipahami siswa karena menggunakan konteks kehidupan sehari-hari. Oleh karena itu, dikembangkan suatu aplikasi pembelajaran mobile berbasis RME pada materi dimensi tiga. Studi ini dilakukan dengan metode penelitian pengembangan ADDIE (Analisa, Desain, Pengembangan, Implementasi, dan Evaluasi). Popluasi dari penelitian ini adalah siswa kelas XII SMA. Hasil penelitian menunjukkan bahwa Mobile Learning Milea D3 telah valid, praktis, dan efektif. Dalam uji coba terhadap sepuluh siswa, media masuk dalam kategori baik, dan hanya satu siswa tidak tuntas belajar. Media pembelajaran Milea D3 tergolong baik dan layak digunakan. Geometry is a branch of mathematics that must be studied. One of the most difficult geometry materials to learn is three dimensions, which requires very high visual and spatial skills. RME is a learning approach that is easy for students to understand because it uses the context of everyday life. Therefore, an RME-based mobile learning application was developed on three-dimensional material. This study was conducted using the ADDIE development research method (Analysis, Design, Development, Implementation, and Evaluation). The population of this research is class XII high school students. The results of the research show that Mobile Learning Milea D3 is valid, practical and effective. In a trial of ten students, the media was included in the good category, and only one student did not complete the study. Milea D3 learning media is quite good and suitable for use.Keywords: Three Dimenssion; Mobile Learning; RMEMathematics is one of the subjects that must be mastered by students in school, especially in three-dimensional material. Three dimensions is one of the most difficult mathematical materials to learn because it requires high visual-spatial abilities. RME is a learning approach that is carried out using the context of everyday life. This is the reason for developing an RME-based mobile learning application on Three Dimensional material. This research is a development research using the ADDIE model. The steps consist of: Analysis, Design, Development, Implementation, and Evaluations. The results of the research show that the developed media is valid, practical and effective. The test results on 10 students with high, medium and low abilities showed that the media was in the good category with 9 students completing their studies and 1 student not completing their studies. Mobile learning can help students understand shapes and spaces in Three Dimensional material.